Word-final stops in Brazilian Portuguese English: acquisition and pronunciation instruction - Walcir Cardoso (Ilha do Desterro, 2008)
This paper presents current research on the second language acquisition of English phonology and its implication for (and applications to) pronunciation instruction in the language classroom. More specifically, the paper follows the development of English word-final consonants by Brazilian Portuguese speakers learning English as a foreign language. The findings of two parallel studies reveal that the acquisition of these constituents is motivated by both extralinguistic (proficiency, style) and linguistic (word size, place of articulation) factors, and that the process is mediated by an intermediate stage characterized by consonant lengthening or aspiration (Onset-Nucleus sharing). Based on these results, I propose that the segments and environments that seem to delay coda production (i.e., monosyllabic words, labial and dorsal consonants) should be given priority in pronunciation instruction. Along the lines of Dickerson (1975), this paper proposes (what we believe is) a more effective and socially realistic pedagogy for the teaching of English pronunciation within an approach that recognizes that "variability is the norm rather than the exception" in second language acquisition.